Mechanical and Thermal Properties of Single-Walled Carbon Nanotube Filled Epoxidized Natural Rubber Nanocomposite - Mohd Abid, Mohd Asyadi Azam; Talib, Elyas; Mohamad, Noraiham; Kasim, Mohd Shahir; Abd Rashid , Mohd Warikh (Asian Network for Scientific Information, 2014)
The use of Single-Walled Carbon Nanotube (SWCNT) as a reinforcement in rubber nano composite nowadays attracts a great deal of attention. Rubber used in this study was Epoxidized Natural Rubber (ENR) and was incorporated with SWCNT as nano filler. The influence of SWCNT nanofiller on mechanical and thermal properties of the produced nanocomposite was studied. The nanocomposite were prepared by using Haake internal mixer with 0, 5, 10 and 15 parts per hundred rubber of the SWCNT and the detailed preparation method is presented. Mechanical properties were evaluated by means of tensile and hardness tests under different SWCNT composition. As results, the strength and elongation at break of the nanocomposite decreased and simultaneously, the strength modulus and hardness increased. Moreover, from the differential scanning calorimetry analysis, the value of melting temperature (Tm), crystalline temperature (Tc) and heat transition (ΔH) were found increased with the increasing ratio of SWCNT.